Quality Assurance Process Development and Improvement A case study Evaluating and Proposing Improvements in a Complaint Handling Process within Product Quality Assurance - Karande, Neeraj P.; Troiza, Carl M.H. (My University, 2024)
As established by existing research, effective complaint handling is crucial for maintaining high product quality and customer satisfaction in product quality assurance. This thesis report adds to this research topic by investigating how to improve a case specific complaint handling process by connecting observations found with principles and concepts in knowledge sharing, information handling, change management, and organisational structure and design. The goal of this thesis has been to identify the challenges in the complaint handling process studied and to make use of the above-mentioned principles to provide recommendations and improvements for the same. This has been achieved by performing a single case study wherein both qualitative and quantitative data was collected in connection with a participation approach. As a result of utilising a combination of qualitative and quantitative research, cross checking between findings was enabled and researcher bias could be mitigated. Various challenges facing the complaint handling process studied could be found, including inconsistency in response times, lack of standardised procedures, and inadequate communication channels. Understanding these operational challenges was found crucial for identifying opportunities for improvement. Furthermore, it was found that designing a structure that aligns with the complaint handling goals and customer centric values of the company is essential for enhancing responsiveness and problem-solving capabilities. Moreover, knowledge sharing and continuous improvement were, through the case process studied, shown to be integral to optimising complaint handling processes and embracing a culture of continuous improvement. The case study performed, coupled with established research, further indicated that such quality and customer-oriented cultures within complaint handling processes further enable organisations to evolve and adapt to changing customer needs and market trends. Furthermore, findings successfully allowed for recommendations to be formulated on how complaint handling processes experiencing similar process environments, to that of the one studied, can promote improvement initiatives and drive performance improvements. It was additionally found that by leveraging insights from the above-mentioned principles, it is possible for organisations to enhance complaint resolution efficiency, elevate customer satisfaction, and drive overall operational success. Lastly, it has been established in this work that since this thesis has been limited to a single case and its operations, generalisation is limited. Thus, some conclusions that have been made in this work are acknowledged limited in their usefulness outside of complaint handling. However, as stated, findings are believed to be of use in those specific cases experiencing similar characteristics to the one studied. As a next step, avenues for future research have been identified, and the findings presented in this work are believed to be promising for the purpose of presenting future research with an additional source to stand on in areas of continuous improvement and complaint handling.
Keywords: Complaint Handling; Complaint Management; Quality Assurance; Knowledge Management; Change Management; Organisational Structure and Design; Continuous Improvement